Economic Evaluation of Screening for Polyomavirus Infection in Kidney Transplant Recipients: A Cost-Utility Analysis. Issue 5 (15th April 2022) - Wong, Germaine; Myint, Thida Maung; Lee, Yoon Jae; Craig, Jonathan C.; Axelrod, David; Kiberd, Bryce
Abstract : Background: Screening for polyomavirus infection after kidney transplantation is recommended by clinical practice guidelines, but cost-effectiveness of this strategy is uncertain. The aim of this study was to estimate the incremental costs and benefits of routine screening for polyomavirus infection compared with no screening in kidney transplant recipients. Methods: Probabilistic Markov models were constructed to compare the health and economic benefits of routine screening for polyomavirus infection using real-time polymerase chain reaction assay. A series of 1-way and probabilistic sensitivity analyses were conducted to define the most influential variables in the model. Results: Monthly screening for 6 mo followed by 3 monthly screenings until 12 mo after transplant was dominant (lower costs and improved outcomes). Compared with no screening, the incremental benefits of screening were 0.294 life-years saved and 0.232 quality-adjusted life-years saved. Total savings from screening were $6986 Australian dollars ($5057 US dollars). The cost-effectiveness ratios were most sensitive to the costs of transplantation and dialysis, age of transplantation, prevalence of viremia, and probability of death in patients with a history of polyomavirus-associated nephropathy. Probabilistic sensitivity analysis indicated that screening (compared with no screening) was the dominant strategy across all plausible ranges of transition probabilities. Conclusions: Screening for polyomavirus infections 1 year following transplantation appears to save money, improves survival, and improves quality of life in kidney transplant recipients.